Characterisation of copper slag in view of metal recovery. (June 2015) - Wang, X.; Geysen, D.; Padilla Tinoco, S. V.; D'Hoker, N.; Van Gerven, T.; Blanpain, B.
Abstract : In this study, the copper bearing particle of a fayalitic copper slag was assessed using quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) and X-ray computed tomography (CT). The copper content of the slag was ∼0·87 wt-%. Copper in this slag was present as sulphidic droplets. The content and particle size distribution of the major sulphide phases (bornite, chalcopyrite and chalcocite/digenite) were quantified using QEMSCAN. The copper bearing particles had a wide particle size distribution from a few micrometres up to millimetre level. Large copper bearing particles (>100 μm) were composed mainly of bornite and chalcocite/digenite and tended to accumulate in the lower part of the slag layer. As characterised with CT, ∼70% of the copper value was present in these large copper bearing particles.